An Interstitial 20q11.21 Microdeletion Causing Mild Intellectual Disability and Facial Dysmorphisms - Ivan Y. Iourov; Svetlana G. Vorsanova; Oxana S. Kurinnaia; Yuri B. Yurov (Case Reports in Genetics)
We report a case of an interstitial chromosome 20q11.21 microdeletion in a 7-year-old male child presenting with mild intellectual disability and facial dysmorphisms. Array comparative genomic hybridization (CGH) has shown that the deletion resulted in the loss of 68 genes, among which 5 genes (COX4I2, MYLK2, ASXL1, DNMT3B, and SNTA1) are disease causing. The size of the deletion was estimated to span 2.6 Mb. Only three cases of deletions encompassing this chromosomal region have been reported. The phenotype of the index patient was found to resemble the mildest cases of Bohring-Opitz syndrome that is caused by ASXL1 mutations. An in silico evaluation of the deleted genomic region has shown that benign genomic variations have never been observed to affect the ASXL1 gene, in contrast to the other disease-causing genes. As a result, it was suggested that ASXL1 loss is likely to be the main cause of the phenotypic manifestations. The present case report indicates that a loss of the disease-causing gene can produce a milder phenotype of a single gene condition.